Exploring cheese and red wine pairing by an in vitro simulation of tasting - Alessandra Rinaldi; Giovanna Bifulco; Alessandra Luciano; Luigi Picariello; Luigi Moio; Raffaele Marrone; Giuseppe Campanile; Angelita Gambuti (Current Research in Food Science)
The cheese wine pairing is a beloved combination subject to a certain subjectivity due to sensorial, psychological, chemical, and cultural factors. This work represents a first attempt to explore the in vitro interactions between cheese, wine, and saliva to objectively measure the pairing. Two experimental red wines obtained from the same grape cultivar and four different cheeses were studied for their composition. Binding reactions between wine and cheese were carried out in three simulated tasting trials and, after precipitation, the wine phenolic content, Saliva Precipitation Index (SPI), and total proteins were evaluated. The optimal pairing (OP) was calculated considering the decrease in salivary and cheese proteins by wine, defined as the cleansing effect; the decrease in astringency due to the cheese, measured by the SPI, and the coating fat which would remain in mouth after eating a piece of cheese. Based on obtained results, the semi-hard cheese was identified as the best pairing option for the two experimental red wines. The differences in the phenolic content between the two wines were instead not enough to show a significant influence on the OP. The in vitro cheese wine pairing can contribute to understanding of wine tasting but it is only a part of the puzzle. However, this first contribution paves the way for additional studies on the molecular and chemical interactions involved in aroma and textural perception in simulated trials.